Faint extended structures near galaxies: preliminary results from the Wise Observatory. Issue Volume 11:Issue S321(2015) (21st March 2017) - Brosch, Noah; Mosenkov, Aleksandr; Rich, R. Michael
Abstract: We present the first results from a survey of deep imaging of edge-on galaxies, with the goal of testing the growth-by-accretion of galaxies proposed by ΛCDM. The data were obtained with a new telescope at the Wise Observatory. Our images show previously unreported extensions of the disk, tidal distortions, and streams at the level of 27-28 mag arcsec −2 .